HIV-1 drug resistance during the transition from NNRTI- to INSTI-based therapy in Thailand: prevalence, resistance-associated mutations, and antiretroviral - Trakulkaseamsiri, Srivilai; Surinkaew, Sirirat; Utthapa, Supanida; Chumchujan, Kittipong (Journal of Associated Medical Sciences, 2026)
Background: Antiretroviral therapy (ART) effectively suppresses HIV replication and reduces HIV-related morbidity and mortality; however, HIV drug resistance (HIVDR) remains a major challenge to long-term treatment success. Objectives: This study investigated the prevalence of HIVDR, resistance-associated mutations (RAMs), antiretroviral susceptibility profiles, and factors associated with HIVDR among HIV-infected patients receiving ART at Queen Savang Vadhana Memorial Hospital, Thailand. Materials and methods: A retrospective study was conducted among 261 HIV-infected patients with HIV RNA levels >1,000 copies/mL who underwent HIVDR testing between January 2020 and December 2024. Drug resistance was determined using next-generation sequencing (NGS)-based assay simultaneously analyzes the protease (codons 1-99), reverse transcriptase (codons 1-376), and integrase (codons 1-288) regions of the HIV-1 pol gene. Variant-calling thresholds were 20% was applied to samples with HIV RNA ≥1,000 copies/mL, 5% was used for samples with HIV RNA ≥15,000 copies/mL, and resistance interpreted using the Stanford HIV Drug Resistance Database (HIVdb version 9.4). Results: Among 261 patients, 169 (64.8%) harbored genotypic drug resistance mutations. CRF01_AE was the predominant HIV-1 subtype (93.1%). Dual resistance to nucleoside reverse transcriptase inhibitors (NRTIs) and non-nucleoside reverse transcriptase inhibitors (NNRTIs) was the most common resistance pattern (49.7%), followed by NNRTI-only resistance (24.3%). NNRTI resistance was the most prevalent resistance class (85.8%), followed by NRTI (65.1%), protease inhibitor (PI) (17.8%), and integrase strand transfer inhibitor (INSTI) resistance (4.1%). M184V and K103N were the most frequently detected NRTI- and NNRTI-associated mutations, respectively. Resistance to nevirapine, efavirenz, and abacavir was common, whereas susceptibility to darunavir/ritonavir, dolutegravir, and bictegravir remained high. Patients with CD4 counts <100 cells/μL and ART duration of 5-10 years were more likely to harbor drug resistant HIV strains, whereas second-line ART was associated with lower odds of HIVDR. Conclusion: Combined NRTI-NNRTI resistance remained the predominant HIVDR pattern during 2020-2024. Although INSTI-associated resistance emerged following the implementation of INSTI-based therapy in Thailand, its prevalence remained low, supporting the continued effectiveness of dolutegravir-based regimens. Continuous HIVDR surveillance remains essential to optimize long-term treatment outcomes.